If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2b-6=6+4b
We move all terms to the left:
2b-6-(6+4b)=0
We add all the numbers together, and all the variables
2b-(4b+6)-6=0
We get rid of parentheses
2b-4b-6-6=0
We add all the numbers together, and all the variables
-2b-12=0
We move all terms containing b to the left, all other terms to the right
-2b=12
b=12/-2
b=-6
| -5(n-3)=9-4n | | 12x+25=3x+10 | | P(x)=11.5x-0.1x-150 | | P(x)=11.5x-0.1-150 | | (18-2x)(29-2x)=152 | | 2(5x-3)-(2x-4)=-(6x=1) | | 5x-3(x+2)=-7+2(x-3) | | x+3(-19/11)=-6 | | 1/2x+8-6=4 | | 11x+15=5x-19 | | -(8+3x)+5=2x+5 | | .30x+140=x | | 3(x+2)+9=42 | | -10k−6=9−7k−8k | | -(8+3x)+5=2x | | 41-21x+12x=44 | | 3y+9=9 | | 3(7x-5)+3(6-4x)-4(2x+4)=-4 | | 36(-3)+x-55=-156 | | 2n-4=6+4n | | 5(x)+24-65=79 | | -4=6+2n | | 6(-3v+1)=5(-22 | | 2(5x-3)-(2x-4)=5-(6x=1) | | 66=3u+15 | | -0.4n=3.2 | | (15x+3)=108° | | -12=-48v | | 9x-40=8x+40 | | 7p+8=5p+4p | | 3(5+c)=2(c-5 | | 10=2u-16 |